2011
DOI: 10.1097/rli.0b013e3181f9c487
|View full text |Cite
|
Sign up to set email alerts
|

Double-Dose Gadoxetic Acid-Enhanced Magnetic Resonance Imaging in Patients With Chronic Liver Disease

Abstract: administration of double dose of Gd-EOB-DTPA provided better arterial enhancement of hepatocellular carcinomas in patients with chronic liver disease, and also improved the lesion-liver contrast in hepatocyte-phase images in patients with Child-Pugh class B disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 21 publications
4
49
1
Order By: Relevance
“…It is possible that the previous study could not demonstrate a difference in lesion-to-liver CNRs between 0.025-and 0.05-mmol/kg doses because we used a suboptimal flip angle (12°). 21 Further, the difference in results between the previous and current studies can be explained by the homogeneity of the study subjects; in this study, we assessed volunteers and not patients with cirrhosis and muscle rather than liver lesions as the object.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…It is possible that the previous study could not demonstrate a difference in lesion-to-liver CNRs between 0.025-and 0.05-mmol/kg doses because we used a suboptimal flip angle (12°). 21 Further, the difference in results between the previous and current studies can be explained by the homogeneity of the study subjects; in this study, we assessed volunteers and not patients with cirrhosis and muscle rather than liver lesions as the object.…”
Section: Discussionmentioning
confidence: 78%
“…17 A recent intraindividual comparison of 0.025 and 0.05 mmol/kg in patients with cirrhosis suggested significant improvement of liver-to-lesion (hepatocellular carcinoma) contrast in patients with decreased hepatic function (Child-Pugh class B disease) but not in patients with preserved hepatic function (Child-Pugh class A disease). 21 A study performed in the early stages of gadoxetic acid development also showed that liver-to-lesion contrast during the hepatobiliary phase was not necessarily higher using 0.05 compared with 0.025 mmol/kg, although the degree of enhancement compared to precontrast images was consistently higher using 0.05 mmol/kg. 16 Our estimates of gadoxetic acid concentration in the liver during the hepatobiliary phase (Fig.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Doubling the dose of Gd-EOB-DTPA has also been suggested. In a study of patients with cirrhosis and hepatocellular carcinomas (HCC), it has been shown that doubling the dose improves the tumor-to-liver contrast during the arterial phase in all patients and during the hepatobiliary phase in Child B patients [12].The clinical impact of this policy in terms of lesion detection remains unknown.…”
Section: Characteristics Of Gd-eob-dtpamentioning
confidence: 99%
“…13,17 However, there is little information on the optimal time delay after the arrival of the contrast agent to the aorta. Researchers have used delay times ranging from 7 to 15 s. 17,[20][21][22] If bolus timing cannot be manipulated as described above, timing may instead be adjusted via the test-injection method, in which a small amount (e.g., 0.5 mL) of contrast agent is injected before dynamic study to measure the length of time for the agent to reach the aorta.…”
Section: Acquiring Images During the Optimal Arterial Phase Time Windowmentioning
confidence: 99%